CHARACTERISTIC OF CHRONIC COMPLICATIONS IN TYPE 2 DIABETIC PATIENT BASED ON ASIAN PERSPECTIVE - Corina Ong (Current Internal Medicine Research and Practice Surabaya Journal, 2022)
Introduction: Indonesia is in the 6th place with the most diabetes mellitus cases in the world. Long term exposure of hyperglycemia that can be seen in chronic type 2 diabetes mellitus patient can cause macrovascular and microvascular complications. This complication contributes to increase mortality rate in Indonesia. Methods: This study uses cross sectional study by studying the medical record of type 2 diabetes mellitus patients, such as age, duration of diabetes mellitus, HbA1C levels, blood pressure, lipid profile, macrovascular and microvascular complication. The data obtained is reviewed descriptively. Results: Most of type 2 diabetes mellitus patient is between 55-64 years (39.4%), mean 55.75 (SD=9.7). Most of the patients suffers type 2 diabetes mellitus for ≥5 years (61%). Meanwhile, the number of type 2 diabetes mellitus patients with uncontrolled HbA1C levels (≥7.0%) is 79%, mean 8.4 (SD= 1.8). Most of type 2 diabetes mellitus patients do not experience hypertension (77.8%) and experience dyslipidemia (94.3%), with the most prevalent lipid abnormality is high LDL (30.9%). Besides, most of type 2 diabetic patients have microvascular complications (57%), with the most common complication is diabetic neuropathy (45.6%), and the other microvascular complications are diabetic nephropathy (33.7%) and diabetic retinopathy (20.7%). While macrovascular complications is 43%, with the most common complication is diabetic foot (29.9%), and the other macrovascular complications are coronary heart disease (27.8%), peripheral arterial occlusive disease (22.9%), and stroke (19.4%).